Irradiation enhanced the anti-friction performance of GO and FND codispersed nanofluids. (December 2022) - Bai, Ming-jie; Liu, Jin-long; Jiang, He; Li, Wen-jun; Wei, Jun-jun; Chen, Liang-xian; Miao, Jian-yin; Li, Cheng-ming
Abstract: Efficient lubrication technology is the basic method of ensuring the energy-saving and long-term stable operation of mechanical equipment. In particularly, it is difficult for a single lubricating solid phase to satisfy the anti-friction and wear resisting requirement of pumps in spacecraft. In this paper, two solid lubrication additives, graphene oxide (GO) and flake nanodiamond (FND), were added into water to form nanofluids, and their lubrication and irradiation properties were studied. Long-term stable GO-FND nanofluids were prepared by a two-step method. The friction test was carried out by a UMT5 tribometer. The irradiation experiment was carried out in the space charged particle irradiation environment simulation equipment. The mixed addition of GO and FND increased the anti-friction effect of nanofluids. The GO/FND nanofluids showed a 42.3 % reduction in the friction coefficient under the Al2 O3 -Si3 N4 friction pairs. After irradiation, the lubrication stability of GO/FND nanofluids was further improved, and the friction coefficient decreased by 78.6 % compared with that of the base fluid. The excellent lubrication performance is attributed to the combined effect of GO and FND. After the friction test, graphene oxide was rolled up around the diamond particles to form a composite carbon film on the surface of the friction pair. The friction reduction effect was improved by forming a fluid film between the friction pair and fluid molecules. Electron irradiation treatment promotes the generation of hydrophilic CO bonds on the carbon nanoparticle surface, increases the affinity between carbon nanoparticles and deionized water, and further reduces the friction coefficient. Graphical Abstract: ga1 Highlights: A composite lubrication nanofluids composed of flake diamond and graphene was developed. The friction coefficient was decreased by 78.6 % after high-energy electron irradiation. The CO bonds on both graphene and diamond surface were enhanced by electron irradiation. The corresponding nano friction mechanism of GO-FND nanofluids was discussed.